Evaluation of the efficacy of the ROGA surgical guide and the freehand technique in the three-dimensional positioning of the implant in patients of the Centro Odontológico de la Universidad Católica de Santa María de Arequipa 2019. - Roxana Gamarra Ojeda (2020)
The success of a rehabilitation on implants lies in the correct three-dimensional positioning of the implant and a surgical guide that has been previously planned with a resale protocol brings us closer to that objective; the ROGA surgical guide is created that aims to be more effective than the freehand technique in such positioning; To evaluate it, 8 implants were placed with ROGA Guide and 8 implants freehand, and then the three-dimensional positioning was evaluated using the before and after tomographs, 5 measurements, mesiodistal and palatal vestibule both at coronal level and at apical and apicocoronal level were evaluated ; the implants placed with the ROGA guide did not have any deviation at the coronal mesiodistal level and in the other measures they had less deviations in relation to the reverse planning with an average of 0.457mm unlike the raised hand that had an average deviation of up to 1 , 91 mm ;; statistically significant difference was found in the other measures there was no statistically significant difference. However, in implants a small millimeter deviation can affect the rehabilitative treatment. It was concluded that the ROGA guide is more effective in the three-dimensional positioning of the dental implant.